Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/nu11040855
|View full text |Cite
|
Sign up to set email alerts
|

Common Habits, Adverse Events, and Opinions Regarding Pre-Workout Supplement Use Among Regular Consumers

Abstract: The purpose of the present study was to examine characteristics of multi-ingredient pre-workout supplement (MIPS) users, their common patterns/habits of MIPS ingestion, and their associated feelings about the effectiveness and safety of this class of supplements. An online electronic survey was distributed through social media to assess self-reported supplementation practices and preferences among adult males and females who reported regular MIPS use. A total of 1045 individuals responded, with 872 of these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Caffeine and these additional substances (capsicum, tyrosine, Mucuna pruriens, green coffee bean extract, Coleus forskohlii, and l-carnitine) are combined in a popular [26] pre-workout supplement (Cellucor, Bryan, TX, USA) that appears to be marketed toward females. The purported effects of this pre-workout supplement include increased lipolysis, transport, and utilization of fatty acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine and these additional substances (capsicum, tyrosine, Mucuna pruriens, green coffee bean extract, Coleus forskohlii, and l-carnitine) are combined in a popular [26] pre-workout supplement (Cellucor, Bryan, TX, USA) that appears to be marketed toward females. The purported effects of this pre-workout supplement include increased lipolysis, transport, and utilization of fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey by Jagim et al [26] examined the supplementation practices of 872 pre-workout users and reported that many consume more than one dose at a time and over 35% do not follow the recommended dosing instructions. Despite this, 85% of these individuals indicated that they believe consuming pre-workout, at their regular dose, is safe [26]. In addition, there are limited data regarding the influence of pre-workout supplements at these doses on metabolic, cardiovascular, and psychological variables in female populations.…”
Section: Introductionmentioning
confidence: 99%
“…We have not taken into account the habit of some sports supplement users to use higher doses than the manufacturer specifies. In a study of users of pre-workout formulas, 14% of them admitted to exceeding the recommended maximum amount by a factor of two or more (Jagim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Multi-ingredient preworkout supplementation has become a popular strategy for individuals attempting to improve feelings of energy and focus; muscular strength; endurance; muscle mass; blood flow; and fat loss during resistance and aerobic training, group exercise classes, as well as recreational activities [ 1 ]. Among the major concerns regarding preworkout supplements, however, is the common manufacturing practice of using numerous, relatively obscure ingredients often combined into proprietary blends at unknown quantities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%